Automatic discharge for bankruptcy: reviewing Bankruptcy Act 1967 in Malaysia / Cartaz Ummu Hani Jaiman … [et al.] - Shamsudin, Nur Akmar Shamira; Mohd Zainuddin, Zaidatul Aqilla; Jaiman, Cartaz Ummu Hani; Mohd Fuad, Noor Fadhlin (2013)
A bankruptcy is often seen as the one who caused the debt-virus among the society. It is indeed, an allergic word that has been traumatized among the nation for ages. Although there are several steps had been forwarded however, the numbers keep increasing. A total of 243,823 people have been declared bankrupt in the country as according to the Malaysia Department of Insolvency, between 2005 and June 2012. This can be summarized as about 52 people are declared bankrupt every day compared with 36 in 2007. Due to the reason of non-payment of business loans, housing, personal, or car loans the people below 45 are the conqueror of this statistics and this is of no good. Thus, in enhancing the law that has been implemented, several provisions need to be reviewed as to erase this lacuna and several countries were made as a reference to comprehend our legislation. Generally, these two ways of discharging and annulling the procedure would not suffice the objectives of lessen the statistics. Although in such a way, the financial institution may make serious effort to assist the borrower, then in initiating the bankruptcy proceeding is not going to be the first at a time. Plus, several consideration need to be taken on when only the Director General of Insolvency (DGI) has to act upon and also the right of being a bankrupt.